2008
DOI: 10.1007/s00421-008-0728-4
|View full text |Cite
|
Sign up to set email alerts
|

IL6 (-174) and TNFA (-308) promoter polymorphisms are associated with systemic creatine kinase response to eccentric exercise

Abstract: Exertional rhabdomyolysis is a complex and poorly understood entity. The inflammatory system has an important role in muscle injury and repair. Serum creatine kinase (CK) is often used as systemic biomarker representing muscle damage. Considerable variation exists in CK response between different subjects. Genetic elements may act as predisposition factors for exertional rhabdomyolysis. Based on their biological activity, we hypothesized that in healthy subjects IL6 G-174C and TNFA G-308A promoter polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 40 publications
6
81
1
4
Order By: Relevance
“…Recently, it was reported that the IL-6 G-174 C genotype is associated with CPK activity in a dose-dependent fashion [40]. Individuals with one or more of the C allele had reduced exercise-associated IL-6 production, reduced post-exercise anti-inflammatory response, and as a result, higher post-exercise CPK peak, compared with individuals homozygous for the G allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that the IL-6 G-174 C genotype is associated with CPK activity in a dose-dependent fashion [40]. Individuals with one or more of the C allele had reduced exercise-associated IL-6 production, reduced post-exercise anti-inflammatory response, and as a result, higher post-exercise CPK peak, compared with individuals homozygous for the G allele.…”
Section: Discussionmentioning
confidence: 99%
“…The IL6-174 G/C polymorphism is associated with power sports performance, with the G allele exerting a favorable effect without an effect on endurance performance [33]. This could be due to the G allele-associated improved muscle repair response after eccentric damage [40]. The NOS3 gene encodes NO synthase.…”
Section: Genetic Profilementioning
confidence: 99%
“…Dear Editor, Yamin and colleagues recently reported an association of a common single nucleotide polymorphisms (SNP) in the promoter region of interleukin-6 (IL6) gene creating a change from a G to C at position -174, and that of tumor necrosis alpha (TNF) gene creating a change from a G to A at position -308 with systemic creatine kinase response to eccentric exercise (Yamin et al 2008).…”
mentioning
confidence: 99%
“…However, in the paper Yamin et al (2008) erroneously refer to this polymorphism with a NCBI reference SNP ID rs13447445, which is in fact located at position -61 of the IL6 gene, and not at position -174 with an ID rs1800795. Similarly, the TNF SNP -308 investigated by the authors should be referred with rs1800629, and not with rs361525 which is located at position -238.…”
mentioning
confidence: 99%
See 1 more Smart Citation